THE EFFECT OF TAXPAYER AWARENESS, QUALITY OF SERVICE, AND TAX SANCTIONS ON TAXPAYER COMPLIANCE IN THE OFFICE WITH SAMSAT JAKARTA EAST - Nurfathir Rizkiani (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to analyze the effect of taxpayer awareness, service quality, and tax sanctions on taxpayer compliance in paying motor vehicle taxes at the SAMSAT Joint Office of East Jakarta City. The method used in this research is a quantitative method. The sampling technique is Convenience Sampling. The data analysis technique used is multiple regression analysis. The data was collected by distributing questionnaires. The results of this study are: 1) taxpayer awareness has a positive and significant effect on mandatory compliance. 2) service quality has a positive and significant effect on mandatory compliance. 3) tax sanctions have no effect on taxpayer compliance. 4) Simultaneously taxpayer awareness, service quality, and tax sanctions have a positive and significant effect on taxpayer compliance. The value of R square obtained is 0.422, meaning that taxpayer awareness, service quality, and tax sanctions have an effect of 42.2% on taxpayer compliance in paying motor vehicle taxes. While the remaining 57.8% is influenced by other variables not examined in this study.